Frontispiece: Lighting Up the Plasma Membrane: Development and Applications of Fluorescent Ligands for Transmembrane Proteins. Issue 34 (16th June 2021) - Borgarelli, Carlotta; Klingl, Yvonne E.; Escamilla‐Ayala, Abril; Munck, Sebastian; Van Den Bosch, Ludo; De Borggraeve, Wim M.; Ismalaj, Ermal
Abstract : Receptorflix would ideally enable researchers to visualize any already‐targeted transmembrane receptor at the cell's surface. Tailor‐made fluorescent ligands accessed by coupling pharmacophores to organic fluorescent dyes are successfully employed to image GPCRs, LGICs, and VGICs. Recent advances in fluorescence microscopy and progress in dye synthesis enable their use in distinct techniques and model organisms. Read more about the literature of the last 25 years on the topic, including fluorescent ligand design and subsequent use in fluorescence imaging techniques to study the three most common classes of transmembrane receptors in the Review by S. Munck and E. Ismalaj et al . on 8605 ff.